Noise complaints and transportation inequality assessment - Yıldırım, Yalçın; Arefi, Mahyar (Elsevier Ltd, 2021)
As a self-reporting data source, the 311 non-emergency service reflects the residents’ concerns on various environmental complaints, including noise. This study explores the nexus between noise complaints extracted from this data source and the transportation-related inequality that reflects a wide range of socio-demographic cohorts associated with it in Dallas, Texas. Noise constitutes an inevitable fact of life—especially in denser urban areas, that as this paper reports, reflects social injustice. Drawing from multiple socio-demographic and transportation indicators, this study conducts multiple statistical and spatial analyses in the selected case studies. The findings further identify the explanatory variables relative to noise complaints and their inequality implications. The results confirm that transportation-related factors affect inequality while also operating within specific socio-demographic patterns. The study gleans lessons for transportation and urban planners, policymakers, and local authorities.
Keywords: Emergency services; Transportation planners; Sociodemographics; Urban transportation